2022
DOI: 10.31219/osf.io/qgtzb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Think for Yourself, or Others Will Think for You”: Predicting Belief in Conspiracy Theories with Epistemic Individualism and Critical Thinking Dispositions

Abstract: Epistemic individualism has recently been considered as a potential explanation for critical thinking and conspiracy theories. We propose in this paper to resolve this paradox. In three studies (N = 1952), we investigate the constituents of epistemic individualism, build a scale, and examine how it explains belief in conspiracy theories. The last study also includes critical thinking dispositions and the appeal to authority. Overall, the final version of Epistemic Individual Scale (EIS) shows good reliability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Then, we measured conformity ( α UK = .78; α Pakistan = .63, Mehrabian & Stefl, 1995, see Figure 2 for details on the scale) and self‐reported social information use with two questions previously found to be associated with conspiracy mentality (Tomas et al, 2022, see Figure 2). The questions were presented in a randomized order.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we measured conformity ( α UK = .78; α Pakistan = .63, Mehrabian & Stefl, 1995, see Figure 2 for details on the scale) and self‐reported social information use with two questions previously found to be associated with conspiracy mentality (Tomas et al, 2022, see Figure 2). The questions were presented in a randomized order.…”
Section: Methodsmentioning
confidence: 99%
“…Is their scepticism restrained to mainstream epistemic authorities or is it a manifestation of a general tendency to discount social information? Recent work has shown that conspiracy believers are more likely to be 'epistemic individualists' (Tomas et al, 2022), a mindset that reflects both an exacerbated distrust of social information and a marked confidence in one's own intuitions. For instance, they are more likely to say that the opinion of someone has no value compared with their own experience and that they do not need others to understand the world.…”
mentioning
confidence: 99%
“…In modern times, this need is expressed through active participation in online discussion forums, where conspiracists collect and weigh the evidence for their theories (Klein et al, 2018(Klein et al, , 2019Levy, 2022). Correlational, questionnaire-based evidence, too, suggests they pride themselves on their independent, analytical, and discerning thinking (Georgiou et al, 2021c;Tomas et al, 2022), and on their openness to experience (Swami et al, 2010(Swami et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Is their skepticism restrained to mainstream epistemic authorities or is it a more general manifestation of a distrustful mindset? Recent work has shown that conspiracy believers are more likely to be 'epistemic individualists' (Tomas et al, 2022), a mindset that reflects both an exacerbated distrust of social information and a marked confidence in one's own intuitions. For instance, they are more likely to say that the opinion of someone has no value compared to their own experience and that they don't need others to understand the world.…”
mentioning
confidence: 99%
“…Then, we measured conformity (αUK = .78; αPakistan = .63, Mehrabian & Stefl, 1995, see Figure 2 for details on the scale) and self-reported social information use with two questions previously found to be associated with conspiracy mentality (Tomas et al, 2022, see Figure 2).…”
mentioning
confidence: 99%